Blood pressure responses to the Cold Pressor Test according to body mass index and waist-to-height ratio in adolescents - Francinete Deyse dos Santos; Edna Ferreira Pinto; Ana Regina Leão Ibiapina Moura; Eguinaldo Vinícius de Carvalho Lima; Mariana Ferreira de Souza; Ferdinando Oliveira Carvalho; José Fernando Vila Nova de Moraes (Hospital de Clínicas de Itajubá, 2020)
Objectives: to analyze the blood pressure (BP) values ​​and responses to the Cold Pressor Test (CPT) according to the body mass index (BMI) and the waist-to-height ratio (WHtR). Methods: 166 adolescents of both sexes participated in the study. Participants underwent measurements of body mass, height and waist circumference. BMI and WHtR were calculated. BP was measured before (pre-test), during (test) and after CPT (recovery). The groups were compared using a mixed ANOVA with Bonferroni post hoc, and Odds Ratio calculation. The level of significance was p < 0.05. Results: prevalences of 16.9% of high BMI, 19.9% ​​of increased WHR and 8.4% of pretest BP were found above the recommended. Participants with high BMI had increased systolic BP compared to their normal peers (113.0 ± 11.4 vs. 121.7 ± 11.6 mmHg; p = 0.003). Adolescents with elevated WHR had higher pre-test and recovery systolic BP (pre-test: 113.2 ± 11.4 vs. 119.6 ± 12.7 mmHg; p = 0.021; recovery: 111.9 ± 14.1 vs. 117.4 ± 14.0 mmHg; p = 0.044). Finally, individuals with BMI and WHtR above the recommended had 2.1 (95% CI 0.62 - 7.36) and 2.5 (95% CI 0.77 - 7.91) times, respectively, more likely to have high pre-test BP values. Conclusion: adolescents with increased BMI and WHtR have higher BP values ​​compared to their normal peers.